2005
DOI: 10.4049/jimmunol.175.6.3525
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Impaired CD8+ but Not CD4+ T Cell Cycle Arrest during Priming as a Consequence of Dendritic Cell Interaction with Plasmodium-Infected Red Cells

Abstract: Individuals living in malaria-endemic areas show generally low T cell responses to malaria Ags. In this study, we show murine dendritic cell (DC) interaction with parasitized erythrocytes (pRBC) arrested their maturation, resulting in impaired ability to stimulate naive, but not recall T cell responses in vitro and in vivo. Moreover, within the naive T cell population, pRBC-treated DC were selectively deficient in priming CD8+ but not CD4+ T cells. Indeed, DC that had taken up pRBC were shown for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…In addition, blood-stage parasites seem to evade CD8 1 T cell immunity. That is, dendritic cells that interact with pRBC selectively impair the cell cycles of CD8 1 T cells, but not CD4 1 T cells [29]. In developing vaccines for blood-stage malaria, establishment of strategies for activating CD8 1 T cells specific for the parasites or infected erythrocytes may be essential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, blood-stage parasites seem to evade CD8 1 T cell immunity. That is, dendritic cells that interact with pRBC selectively impair the cell cycles of CD8 1 T cells, but not CD4 1 T cells [29]. In developing vaccines for blood-stage malaria, establishment of strategies for activating CD8 1 T cells specific for the parasites or infected erythrocytes may be essential.…”
Section: Discussionmentioning
confidence: 99%
“…In playing such a central role in immunity, it is not surprising that the function of DCs is targeted by the parasite. Indeed, several studies in both humans (5,6) and mice (7)(8)(9)(10)(11)(12)(13)21) have documented changes in DC function in response to Plasmodium. In contrast, other reports have found fully functional DCs when exposed to parasites (14 -20).…”
mentioning
confidence: 99%
“…Studies have found that dendritic cell (DC) 3 function is compromised during Plasmodium falciparum infections and suggested that this was a factor in the pathogenesis of severe disease (1,2). Similarly, studies of rodent P. berghei infections have also found that DC functions are compromised following infection (3)(4)(5) but other studies have found that DCs from mice infected with P. chabaudi or P. yoelii were fully functional (6,7).…”
mentioning
confidence: 99%